Solar charger with power pack on camouflage fabric for field application - Ireneusz Plebankiewicz; Krzysztof A. Bogdanowicz; Wojciech Przybył; Andrzej Wysoczański; Agnieszka Iwan; Krzysztof Górecki (Scientific Reports)
Abstract This paper mainly aimed to construct a solar charger with power pack on camouflage fabric (280 × 305 × 3 mm) for military and civil use in mining and reconnaissance set. The solar charger includes a photovoltaic panel, supercapacitor module (composed of 8 supercapacitors XV series), converter (B10-1224-05) and connectors (SP1312/S2 and SP1312/S4). The constructed solar charger was tested in laboratory and field conditions. In the first stage of our work, we tailored the solar charger based on the receiver the BATTERY Start 400 power bank requirements, portability and modular construction. We performed field trials performance studies in the second stage to confirm the laboratory results. The obtained results of the charger efficiency were satisfactory during unfavourable weather conditions (temporary rainfall, total cloud cover), and we obtained η ≈ 0.9 with periodic cloud cover. The energy delivered during one day of charging t = 9 h was EPB ≈ 38 Wh. This was confirmed by laboratory tests where approximately 80 Ah was stored during 18 h of charging the BATTERY Start 400 energy storage. It was confirmed that the 50 F capacitance of the supercapacitor module allowed the charging of BATTERY start 400 power bank – receiver for up to 22 min when fully charged. Finally, it was shown that the charging and discharging experiments of the proposed system demonstrate the stability against highly volatile weather conditions.